Addition of a foaming agent to improve N2 gas permeability of PVA/alginate carriers for deammonification process. (9th November 2017) - Choi, Daehee; Lee, Dongryeol; Yun, Wonsang; Jung, Jinyoung
Abstract: Long term use of anammox carriers immobilized in PVA/alginate has always faced problem due to expansion and bursting due to dense surface. The physical and morphological characteristics were investigated by adding foaming agent to 0, 0.15, 0.3, 0.6 and 1.2 w/v% to increase the gas permeability. Maximum real and bulk density, minimum specific surface area and swelling ratio were found at 0.3 w/v% foaming agent. The gas permeability increased continuously up to 1.2 w/v% foaming agent, as found in the break point test. The 0.3 w/v% foaming agent gave optimum bacteria retention capacity of 98.9%. With 0 w/v% foaming agent, non-porous outer layer was burst due to pressure of produced nitrogen gas as confirmed by morphology test. Addition of foaming agent caused porous structure and the anammox bacteria grew deep inside the carrier. Therefore, the optimum foaming agent content of 0.3% can greatly enhance process stability in the deammonification system. Highlights: For anammox, PVA/alginate carrier bursting problem solved by foaming agent addition. Maximum density with minimum surface area and swelling ratio at 0.3% foaming agent. Gas permeability increased as foaming agent increased, found in the break point test. 0.3% foaming agent showed an optimum bacteria retention capacity of 98.9%. The anammox bacteria grew inside pores of the carrier made by foaming agent.